2018
DOI: 10.3389/fnagi.2018.00178
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis and Identification of Novel Biomarkers in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a quite common neurodegenerative disorder with a prevalence of approximately 1:800–1,000 in subjects over 60 years old. The aim of our study was to determine the candidate target genes in PD through meta-analysis of multiple gene expression arrays datasets and to further combine mRNA and miRNA expression analyses to identify more convincing biological targets and their regulatory factors. Six included datasets were obtained from the Gene Expression Omnibus database by systematical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 55 publications
4
29
0
Order By: Relevance
“…Interestingly, a link via mitochondrial dysfunction has been made between metabolic syndrome, diabetes, obesity, and non-alcoholic fatty liver disease in the progression of AD, PD, and other neurodegenerative diseases [108]. Furthermore, lipid metabolism (in particular non-alcoholic fatty liver disease pathway) and mitochondrial dysregulation have been identified as molecular pathways and putative biomarkers linked to PD [109]. Post-translational deimination is revealed for the first time for NAFLD associated KEGG pathways in this study and may be of relevance for the interplay of neurodegeneration and such comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a link via mitochondrial dysfunction has been made between metabolic syndrome, diabetes, obesity, and non-alcoholic fatty liver disease in the progression of AD, PD, and other neurodegenerative diseases [108]. Furthermore, lipid metabolism (in particular non-alcoholic fatty liver disease pathway) and mitochondrial dysregulation have been identified as molecular pathways and putative biomarkers linked to PD [109]. Post-translational deimination is revealed for the first time for NAFLD associated KEGG pathways in this study and may be of relevance for the interplay of neurodegeneration and such comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…PAK (p21 activated kinase) is a family of serine/threonine kinases that function as Rac and Cdc42 GTPases effector molecules, and they are implicated in the signal transduction emanating from integrins and tyrosine kinase receptors. Furthermore, PAK has been related to neurodegenerative diseases [ 93 ]. In a healthy brain, PAK is involved in the regulation of neuron viability, synapse morphology and functionality, gene transcription in neurons, microglial motility, microglial immune response, and astrogliosis [ 94 ].…”
Section: Small Gtpases Of the Rho Familymentioning
confidence: 99%
“…It has been demonstrated using post-mortem brain samples that Cdc42 expression is elevated in the prefrontal cortex of AD patients [ 104 ]. Gene expression database analyses have shown that PD patients have reduced Cdc42 mRNA levels [ 93 ]. Together, this data indicates that Cdc42 could play an important role in neurodegeneration.…”
Section: Small Gtpases Of the Rho Familymentioning
confidence: 99%
“…Regarding the to miRNA – target interactions (MTIs) in interatome hDAT and are deregulated in PD, in a previous study of Parkinson’s patients that aimed to the Identification of Novel Biomarkers in PD was carried out as follows approach: i)experimentally supported databases with experimentally verified and ii) different prediction algorithms[13], which allows obtaining the following resulted miRNAs : miR-126-5p, hsa-miR-29b-3p, and hsa-miR-301a-3p which are also described in the present study about this miRNAs and interaction with mRNA previously described that miR-126-5p interaction with CAMK2A [53], EPS15 [53, 54], NEDD4 and SNCA[56], the hsa-miR-29b-3p interaction with EPS15 [57], CDH1 [58], GPR37[59] and the hsa-miR-301a-3p interaction with CSK[60] and EPS15[61] which are also part of hDAT interactome, which although we found miRNAs that interacted with multiple mRNAs of hDAT interactome proteins, which presented altered expression in PD vs controls, we did not find any type of relationship either in the number of miRNAs per target of the interactome, or in the combined estimate of rate of miRNA change and the combined estimate of rate of change in hDAT interactome mRNAs.…”
Section: Discussionmentioning
confidence: 99%